pemberatan PEMBERATAN PIDANA BAGI PELAKU OBSTRUCTION OF JUSTICE DALAM UPAYA MEMBERIKAN DAMPAK POSITIF KINERJA PENEGAK HUKUM - Jodi, Faris Fachrizal (Faculty of Law, Universitas Pasundan, 2024)
In 2023, the universe of social media and television is filled with the term obstruction of justice or obstruction of legal process in the case that killed one of the police officers allegedly by his superiors. In their efforts to eliminate evidence, evidence, and fabricate cases, obstruction of justice was committed, involving several members of police. Obstruction of Justice is a serious thing that can be done by a person who intentionally prevents, hinders, or thwarts directly or indirectly an investigation or criminal legal process. How aggravation of criminal sanctions can be imposed upon as an effort to provide deterrence to the law enforcement who committed obstruction of justice to improve the performance of law enforcement? The approach used in this research is juridical normative. This is an approach that analyzes primary and secondary data. Normative approach is a conceptual approach to legislation, a case approach, and a comparative approach are also applied. The imposition of aggravation of sanctions upon the law enforcement is not only intended to retaliate but also to maintain spirit of National Police as the state representative in the field of investigation because evil acts committed by investigators (culprit) are not only unlawful, but also have damaged the criminal law enforcement system in Indonesia, the good name of the National Police as an investigator, and undermined public trust in the Indonesian criminal justice system. Therefore, criminal punishment is not only to provide a deterrent effect but also to provide efforts to improve the performance of investigators.